Reading Literacy Quality Management to Improve MTs Students’ Competence: Yakpi Wasilatul Huda and Yamisa Soreang–Bandung - A.D. Rima Widianingsih; Eva Dianawati Wasliman (CV. Media Digital Publikasi Indonesia, 2026)
Education in Indonesia emphasises academic development and the formation of students' spiritual character, but the low level of interest in reading among Madrasah Tsanawiyah (MTs) students remains a challenge in improving their competence. This study aims to analyse the implementation of reading literacy quality management in an effort to improve student competency at MTs Yakpi Wasilatul Huda and MTs Yamisa Soreang, Bandung Regency, covering aspects of planning, implementation, evaluation, follow-up, obstacles, and solutions. This study uses a qualitative approach with a case study method, while data is collected through observation, interviews, and documentation studies to obtain a comprehensive picture of the literacy programmes in both madrasahs. The results showed that the planning of the literacy programme was quite thorough, the implementation demonstrated a commitment to developing a culture of literacy, the evaluation focused on student competency achievement as a measure of success, and follow-up was carried out through presentations of students' reading results. The main obstacles found were the limited availability of reading materials that suited the students' needs and the lack of family support, while the solutions were the provision of adequate reading books, the allocation of special reading time, and the provision of opportunities for students to present their reading results. Active participation by teachers and students has been observed, but more systematic and sustainable strategies are needed. The conclusion of this study emphasises that the successful improvement of students' literacy competencies requires targeted quality management through the provision of reading materials, teacher training, and intensive collaboration between schools, parents, and the community, so that literacy programmes not only improve academic abilities but also support the character building of students